The Implementation of Surcharge Charging By Merchants in Non-Cash Transactions at the Representative Office of Bank Indonesia Bali Province - A.A. Sagung Ngurah Indradewi; Made Tamar Martayasa (Journal of Sustainable Development Science, 2024)
This research aims to determine the application of additional fees charged by merchants in non-cash transactions in the Legal Area of ​​the Bali Province Bank Indonesia Representative Office and how the Bali Province Bank Indonesia Representative Office supervises merchants in payment transactions via EDC machines regarding the action of charging fees. addition. Types of empirical legal research. The data collection method uses interview techniques. The results of the research on the implementation of surcharge charges by merchants in non-cash transactions are that there are charges carried out by merchants, because the authority of the Bank Indonesia Representative Office is limited to preventive enforcement, repressive law enforcement in the form of administering administrative sanctions can only coordinate with the Bank Indonesia Representative Supervision Office against merchants. in payment transactions via Bank Indonesia's central EDC machine if there is a report from a disadvantaged party. Supervision of Bank Indonesia Representative Offices on merchants in payment transactions via Electronic Data Capture (EDC) machines related to the action of imposing surcharges in the form of providing socialization, education and administrative witnesses in the form of terminating the Cooperation relationship to the party providing the EDC, ordering the merchant to return funds in the amount of the transaction value which indicates the existence of a charge subcharge fees as a form of protection for consumers if there are consumers who report experiencing losses using debit cards.